Hubungan Manajemen Laba Sebelum IPO dan Return Saham dengan Kecerdasan Investor sebagai Variabel Pemoderasi - JONI JONI; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
The major purpose of this study is to investigate association be-tween earnings management before Initial Public Offerings (IPO) and stock's returns with investors sophistication as a moderating  variable. Institutional ownership is used to proxy investors sophistication. The JSX's IPO companies from 1990 to 2002 were used as samples. The first sample was 75 companies which institutional ownership ? 40% and the second was 63 companies that institutional ownership ? 60%. Instrumental Variable Approach (Kang and Sivaramakrishnan, 1995) was used to detect earnings management.This study provides an evidence that issuers report unusually high earnings management around IPO (two years before and five years after IPO). Issuers used mean reversing strategy in  two years before IPO period (income decreasing) for preparing earnings management in the next period (income increasing). Furthermore, this study documented a negative association between earnings management andstock's re-turns with investors sophistication as moderating variable. One inter-pretation of this finding is that high earnings management has substan-tial stock's returns consequences when investors sophistication factor was taken into account. This finding is consistent  with the prior re-search developed by Balsam et al., 2002.